Development of the Community-Based Treatment and Rehabilitation Model for Drug Addicts at Kudbak Hospital, Sakon Nakhon Province - หาญสุริย์, ธนวรรษ (Journal of Health Science of Thailand, 2024)
The purposes of this research were to (1) explore the conditions and challenges associated with community-based treatment and rehabilitation for drug addicts at Kudbak Hospital in Sakon Nakhon Province, (2) construct and develop a community-based treatment and rehabilitation model, and (3) examine the efficiency of the developed community-based treatment and rehabilitation model. A three-stage approach was developed and organized as follows: phase I examined fundamental information regarding current conditions and challenges of illegal drug use in the Kudbak district and explored ten stakeholders’ opinions regarding conditions and challenges, needs, and successful factors in using community-based treatment and rehabilitation of drug addicts; phase II was related to model construction and development; and phase III involved the efficiency of the developed model. Statistics for data analysis included mean and standard deviation and content analysis. The findings revealed that: (1) the current conditions in the community were overall at a high level ((mean=4.05); while factors related to drug prevention in the community were overall at a moderate level ((mean=3.24). (2) The model components included principles, objectives, systems and mechanics, processes, and evaluation. The developed model was rated at the highest level of appropriateness and feasibility, with a mean score of 4.95. (3) The effectiveness of the developed community-based treatment and rehabilitation model for drug addicts at Kudbak Hospital in Sakon Nakhon Province yielded the following outcomes: all 15 patients (100%) completed the treatment program. After one month of treatment, 100% of the participants had ceased using drugs. This success continued, with 100% of the participants remaining drug-free after three months.